Application of Mu'nah Rahn Tasjily in Land Collateral: Integration of DSN-MUI Fatwa and Sharia Economic Principles - Wasman Wasman; Sekar Elena; Ahmad Khoirudin; Abdul Fatakh; Fajar Setiawan (UIN Siber Syekh Nurjati Cirebon, 2024)
This study investigates the application of mu’nah rahn tasjily in land collateral financing at Pegadaian Syariah KC. Cipto Mangunkusumo Cirebon, integrating the DSN-MUI Fatwa No. 68/DSN-MUI/III/2008 and the Compilation of Sharia Economic Law (KHES). Employing a qualitative approach with a normative-empirical methodology, the research combines literature reviews and field investigations. Primary data were collected through interviews with employees and managers, while secondary data included books, journals, and relevant documents. Data collection methods involved observation, structured interviews, and documentation, focusing on the implementation of mu’nah in land certificate financing for the year 2023. The findings reveal two types of rahn tasjily contracts, with one involving the determination of mu’nah based on the loan amount. In these contracts, the collateral submitted serves only as proof of ownership, while the pledger retains control over the physical collateral. However, an analysis of the DSN-MUI Fatwa indicates a deviation in practice at Pegadaian Syariah KC. Cipto Mangunkusumo, as mu’nah is calculated proportionally to the loan amount rather than independently. Furthermore, the KHES emphasizes time-based calculations for ijarah, suggesting the necessity of structured time limitations to prevent disputes and ensure compliance with Sharia principles. This study underscores the need for a more consistent application of Sharia guidelines in determining mu’nah to enhance transparency and fairness in Islamic financial practices.Keywords: Mu’nah Rahn Tasjily, Land Collateral, DSN-MUI Fatwa, Sharia Economic Law, Islamic Pawnshop Practices.